2022
DOI: 10.1111/jorc.12444
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the practice patterns of nephrology nurse practitioners in Australia

Abstract: Background: Nurse practitioners (NP) have an expanded scope of practice beyond that of a registered nurse. In kidney care, nephrology NP can manage patients at various points along the chronic kidney disease (CKD) trajectory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The argument that ANPs would contribute to the shortage of nurses dismisses their specialized training and capacity to provide comprehensive care. Contrary to this perception, studies [1] from various settings have shown that ANPs enhance healthcare access without depleting the nursing workforce. Their presence can address the diverse healthcare needs of a population while also enhancing the quality of care provided.…”
Section: The Nurse Shortage Mythmentioning
confidence: 82%
“…The argument that ANPs would contribute to the shortage of nurses dismisses their specialized training and capacity to provide comprehensive care. Contrary to this perception, studies [1] from various settings have shown that ANPs enhance healthcare access without depleting the nursing workforce. Their presence can address the diverse healthcare needs of a population while also enhancing the quality of care provided.…”
Section: The Nurse Shortage Mythmentioning
confidence: 82%
“…They also provide education, support patients (and their informal carers) to engage in self-management, as well as support them to make informed health-care related decisions. 18,21 An additional role is outreach from hospitals into primary care practices to educate general practitioners and practice nurses to ensure diagnosis and early intervention, and timely referral to a nephrologist.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…One reason for the positive outcomes seen in nurse practitioner services may be that a major focus is the provision of patient education and patient-centred care. 12 General practitioners and medical specialists have frequently been criticised for suboptimal outcomes. Previous research has shown general practitioners and specialists place significantly less value on information provision and person-centredness, [24][25][26] and often have a poor understanding of patients' health-related priorities.…”
Section: What This Paper Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early 2000s, some literature described the role of nephrology APNs and showed their practice [23][24][25]. Nowadays, nephrology APNs have contributed to improving the healthcare outcomes of patients with all CKD stages who are not yet on dialysis [26][27][28], are on dialysis [29,30], or are pre-or post-kidney transplant [31,32]. We believe it is worthwhile to identify and present such cumulative practice of nephrology APNs.…”
Section: Introductionmentioning
confidence: 99%